PRACTICAL ASPECTS OF ANALYZING THE SUPPLY OF AGRI-FOOD PRODUCTS IN THE CONTEXT OF GLOBAL RISKS AND CHALLENGES TO FOOD SECURITY (Development Service Industry Management, 2025)
In the context of modern global challenges, food security is gaining strategic importance for Ukraine and for countries worldwide. Moreover, this issue is especially acute in the context of the ongoing war since 2014, as such conflicts pose a serious threat to agribusiness and, in general, to the sustainable supply of food to the population. Even though many scientific publications and analytical reports are devoted to ensuring global food security, modern global risks and challenges to food security require further analysis.The article examines the issue of practical aspects of analyzing the supply of agri-food products in the context of global risks and challenges to food security. It is found that food security is the main condition for sustainable growth, since solving its problems guarantees ensuring proper (full-value and high-quality) nutrition for citizens. Considerable attention is paid to the main issues, and specific mechanisms for responding to them are proposed, allowing not only to identify weaknesses in Ukraine's food security system but also to outline ways to overcome them, considering modern risks and challenges. It is determined that both internal and external factors significantly influence the modern agricultural sector. Fluctuations in global markets, climate change, geopolitical instability, pandemics, and other crises create new challenges for the stability of food production, processing, and supply. It is substantiated that coordinated actions at the state, agribusiness, and international partner levels can ensure the stability of the food system and meet the population's needs even in crises. Thus, ensuring food security amid global risks requires a comprehensive, systemic approach that combines economic, technological, social, and environmental instruments.
Keywords: agri-food products; Global Food Security Index; competitiveness; food security; resources; market; agriculture